Wuwei Kushen Changrong capsule alleviates DSS-induced colitis in mice via inhibition of NLRP3 inflammasome and STAT3 pathway - Chen, Mingjun; Feng, Yang; Luo, Dan; Zhang, Chen; Zhou, Jing; Dai, Hengheng; Lin, Mingxiong; Tong, ZhanQi (Frontiers in Pharmacology, 2024)
Purpose: Wuwei Kushen Changrong capsule (Composite Sophora Colon-soluble Capsule, CSCC) is a Chinese patent medicine developed to treat ulcerative colitis. Studies highlight CSCC potential efficacy for ulcerative colitis (UC) but unclear mechanism limits its widely treatment for patients. We aimed to investigate the anti-colitis efficacy of CSCC and explore the mechanism by which GPR43 inhibits the NLRP3/STAT3 signaling pathway, thereby mediating the protective effects of CSCC on the intestinal barrier. Methods: The protective effects of CSCC were evaluated in a murine ulcerative colitis model induced by 3% DSS. Assessments included body weight, Disease Activity Index (DAI) score, colon length, and histopathological score. Colon tissue, cell function, and immuneinflammatory status were evaluated using immunohistochemistry, immunofluorescence, ELISA, and real-time fluorescence quantitative PCR (RT-PCR). Protein expression levels of relevant pathways and receptors were measured using Western blot. All experiments were repeated. Results: CSCC protected mice from DSS-induced colitis by upregulating Gpr43, promoting the expression of ZO-1 and Occludin tight junction proteins. Mechanistically, CSCC inhibits the MEK4/JNK1/STAT3 activation pathway, consequently suppressing the STAT3/NLRP3/IL-1β pathway and inhibiting the production of inflammatory factors such as IL-17A. Conclusion: The mechanisms through which CSCC protects against DSS-induced colitis may include upregulating Gpr43, inhibiting the STAT3/NLRP3 pathway, and suppressing inflammation factors like IL-17A. These findings highlight the mechanisms underlying CSCC's anti-colitis effects and suggest its potential as a therapeutic candidate for managing the progression of UC.